The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/vcp.12743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RNA isolation and library preparation methods for small RNA sequencing of canine biofluids

Abstract: | INTRODUC TI ONMicroRNAs (miRNAs) are highly conserved, small (21-25 nucleotides in length), noncoding RNAs that are present in biofluids such as serum, plasma, and urine. 1 Through the posttranscriptional regulation of mRNA expression, miRNAs control diverse physiological activities. 2 Recently, it has been reported that biofluid-derived miRNAs can serve as novel noninvasive biomarkers for the early detection of cancers, and degenerative and metabolic diseases, as well as therapeutic targets for such conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…RNAseq and dPCR generate relative and absolute quantification of genes through different methodologies, which could explain the mismatch. One potential source of discrepancy is the library preparation process required by RNAseq, but not dPCR 20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RNAseq and dPCR generate relative and absolute quantification of genes through different methodologies, which could explain the mismatch. One potential source of discrepancy is the library preparation process required by RNAseq, but not dPCR 20 …”
Section: Discussionmentioning
confidence: 99%
“…Others normalize quantitative reverse‐transcription PCR (qPCR) to plasma input volume 19 . RNA deep‐sequencing (RNAseq) allows relative and absolute quantification based on normalization across millions of all mapped reads 20 . Digital droplet PCR (dPCR) provides absolute quantification without a normalization gene by measuring tens of thousands of PCR reactions in parallel and assaying against a standard curve for 6‐carboxyfluorescein (FAM) fluorescence 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, research on miR-147 and its role in the development of CKD is lacking. To our best knowledge, this study is the first to document upregulation of miR-147 in CKD, which reemphasizes the importance of an unbiased approach using sequencing technology for miRNA discovery 37 .…”
Section: Discussionmentioning
confidence: 82%
“…Several studies reported the analysis and characterization of exosomes derived from canine-species MSCs and presented differential expression of cytokines and growth factors in adipose tissue- and bone-marrow-derived MSC exosomes [ 55 ]. Research studies using canine reported the comparison of miRNA expression levels in exosomes according to the sources of biofluids, such as serum and urine [ 56 ]. Stem cell-derived exosomes not only exert immune defenses, but also play a crucial antitumor role [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%